Evaluation of the Association of Plasma Pentraxin 3 Levels with Type 2 Diabetes and Diabetic Nephropathy in a Malay Population. (20th November 2013) - Abu Seman, Norhashimah; Witasp, Anna; Wan Mohamud, Wan Nazaimoon; Anderstam, Björn; Brismar, Kerstin; Stenvinkel, Peter; Gu, Harvest F.
Abstract : Recent reports have demonstrated that elevated plasma long pentraxin 3 (PTX3) levels are associated with cardiovascular and chronic kidney diseases. In the current study, we investigated the plasma PTX3 levels in 296 Malay subjects including the subjects with normal glucose tolerance (NGT) and type 2 diabetes (T2DM) patients with or without DN by using an enzyme-linked immune-sorbent assay. Results showed that in males, plasma PTX3 levels in T2DM patients without DN were lower than that in the subjects with NGT (2.78 versus 3.98 ng/mL; P = 0.021 ). Plasma PTX3 levels in T2DM patients with DN were decreased compared to the patients without DN (1.63 versus 2.78 ng/mL; P = 0.013 ). In females, however, no significant alteration of plasma PTX3 levels among NGT subjects and T2DM patients with and without DN was detected. Furthermore, an inverse correlation between PTX3 and body mass index was found in male subjects with NGT (P = 0.012 ; r = - 0.390 ), but not in male T2DM patients, neither in all females. The current study provided the first evidence that decreased plasma PTX3 levels are associated with T2DM and DN in Malay men and also suggested that PTX3 may have different effects in DN and chronic kidney diseases.